SOCIAL PHOBIA AS A FACTOR INFLUENCING ADOLESCENTS’ ADAPTATION TO SOCIAL ENVIRONMENTS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the manifestation, psychological features, and negative consequences of social phobia during adolescence. Social phobia is described as a persistent fear of situations in which a person might be evaluated by others. It is often associated with low self-esteem, a critical self-image, excessive concern about others' opinions, and the lasting presence of negative memories. Adolescents suffering from social anxiety tend to avoid communication with strangers, public speaking, and participation in social interactions. Their social skills are underdeveloped, which may result in difficulties in both academic and personal life. The article highlights that social phobia is not just extreme shyness but a serious psychological condition that can disrupt a person's well-being. Unlike general nervousness, this disorder significantly impacts everyday functioning and requires timely psychological intervention. Findings underline the importance of early detection and the application of appropriate psychological strategies to support adolescents in overcoming the fear of social evaluation and building confidence.